Analisis Efektivitas Sistem Kerja Hybrid dalam Administrasi Pemerintahan di Kementerian Dalam Negeri - Rumahorbo, Graciela Magdalena; Wolor, Christian Wiradendi; Utari, Eka Dewi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the effectiveness of the hybrid work system in public administration, focusing on its implementation within the Ministry of Home Affairs. The research employed a descriptive qualitative approach using a case study method, with data collected through interviews, observation, and documentation. The findings reveal that the hybrid system offers flexibility for administrative tasks but remains suboptimal due to infrastructure limitations, inconsistent implementation across units, and the absence of a standardized performance evaluation system. Employee productivity varies depending on job type, technological readiness, and personal discipline. Key challenges include domestic distractions during remote work, limited access to physical documents, and uneven organizational support. Therefore, the hybrid work system requires stronger policy support, technology investment, and organizational culture reform to be implemented effectively and sustainably.